Biblioteka krymskotatarska w Symferopolu - Janczak, Barbara (Biblioteka Uniwersytecka w Poznaniu, 2016)
Artykuł jest próbą przedstawienia procesu odradzania się biblioteki narodowej krymskotatarskiej mniejszości etnicznej w wieloetnicznym środowisku Krymu. Omówiono ważniejsze wydarzenia z ponad 25-letniej historii tworzenia biblioteki oraz jej obecną strukturę i działalność: prace biblioteczne, usługi, działalność oświatową, metodyczną, naukową i wydawniczą.

The article is an attempt to present the process of revival of the Crimean Tatar ethnic minority’s national library in the multiethnic society of Crimea. The most important events from the over 25-year-long history of the Library are discussed alongside with a description of its current structure and functions, procedures and activities, including available services, library processes, as well as its educational, methodological, scientific and editorial activity.
Crimean Tatar Library in Simferopol
Keywords: Krym; Crimea; Tatarzy krymscy; Crimean Tatars; Republikańska Biblioteka Krymskotatarska im. I. Gasprinskiego; Ismail Gasprinsky Republican Crimean Tatar Library; funkcje biblioteki; library functions; usługi biblioteczne; library service